Goddess ‘name’ or name of a goddess? Astarte and her epithet on the stela of Betu (TBO 760) - Meyrat, Pierre (Ägypten und Levante, 2020)
New interpretation for the three hieroglyphs following the name of Astarte on the stela of the overseer of horses Betu discovered at Tell el-Borg in 2006. In all likelihood, these signs form a variant writing for the name of an Egyptian goddess. The resulting syncretic combination is discussed.